Improving oral health of institutionalized older people with diagnosed dementia - Zenthöfer, Andreas; Cabrera, Tomas; Rammelsberg, Peter; Hassel, Alexander J. (Aging & mental health, 2016)
Objective: Previous research has revealed poor oral hygiene and health among older people suffering from dementia. To evaluate the oral health and denture hygiene of older people with and without dementia, six months after carer have followed a dental education programme.Method: Ninety-three older people living in four long-term care homes in south-western Germany were included in this longitudinal cohort study. All participants were allocated into two groups on basis of the medical dementia diagnosis extracted from the medical records in the care documentation: suffering from dementia (n = 33) or not (n = 60). For each participant plaque control record, gingival bleeding index (GBI), community periodontal index of treatment needs (CPITN), and denture hygiene index (DHI) were assessed at baseline and six months after carer have followed a dental education programme, and after use of ultrasonic devices for denture cleaning. Differences between all target variables from baseline to follow-up, and between participants with and without dementia, were evaluated by bivariate and multivariate testing.Results: In bivariate testing, participants with dementia had a significantly lower DHI (p < 0.001), a lower GBI (p < 0.05), and a lower CPITN (p < 0.01) at follow-up. In participants without dementia, only for DHI (p < 0.001) a significant improvement was observed. In multivariate analyses, the significant association could not be reproduced (p > 0.05).Conclusions: Use of ultrasonic baths can be a successful means for improving denture hygiene among older people in long-term care with and without dementia. Education for carer in order to improve oral hygiene, however, seems to be of minor significance and to be more effective for people with dementia.